2015
DOI: 10.1016/j.cattod.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C2+ hydrocarbons by CO2 hydrogenation over the composite catalyst of Cu–Zn–Al oxide and HB zeolite using two-stage reactor system under low pressure

Abstract: The combination of methanol synthesis and methanol-to-gasoline (MTG) reaction is a beneficial process to produce particular C 2+ hydrocarbons from CO 2 and H 2 , because MTG reaction can produce C 2+ hydrocarbons selectively without the formation of methane. However, the composite catalysts consisting of methanol synthesis catalyst and zeolite previously reported have produced C 2+ hydrocarbons in poor yields especially under low pressure conditions. This paper reports the high yield production of C 2+ hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…The preservation of the strong acid sites of the modified HB zeolite with hydrophobic surface improved the second-step CH 3 OH conversion activity. 143 …”
Section: Co 2 Hydrogenation To C 2+ ...mentioning
confidence: 99%
“…The preservation of the strong acid sites of the modified HB zeolite with hydrophobic surface improved the second-step CH 3 OH conversion activity. 143 …”
Section: Co 2 Hydrogenation To C 2+ ...mentioning
confidence: 99%
“…Analysis of the literature data showed that to date, noticeable activity in the hydrogenation of carbon dioxide to C2+ hydrocarbons has been established mainly for iron-containing catalysts with an oxide base [85][86][87]. In [88][89][90], C2+ hydrocarbons is characteristic of ironcontaining catalysts, while the Co and Ni catalysts selectively gave higher CH4 yields than other catalysts.…”
Section: Hydrogenation Of Carbon Dioxide To C2+ Hydrocarbonsmentioning
confidence: 99%
“…and methanol-to-alkane transformation Alkane products can also be obtained through cascade Reproduced with permission from © 2017 Royal Society of Chemistry. catalysis combining methanol synthesis from CO2 hydrogenation, and a subsequent MTH reaction 70,93 . Typical catalysts for the methanol synthesis from CO2/H2 include Cu-based materials (Cu supported on ZnO 94 , Ga2O3 95 , ZrO2 96 ) and noble metals (Pd 97 , Pt 98 , Au 99 , Ag 100 ), while the commonly used catalysts for the MTH process are zeolites 101 .…”
Section: Bifunctional Catalysts For Both Methanol Synthesismentioning
confidence: 99%